THE INFLUENCE OF FERTILIZER TYPE AND Trichoderma harzianum INOCULATION ON THE GROWTH AND PHYSIOLOGY OF YOUNG PLANTS OF Cordia americana - Andriguetto, Kellin Vanessa; Waimer, Gabriel Coelho; Silva dos Santos, Breno Magno; Turchetto, Felipe; Griebeler, Adriana Maria; Araujo, Maristela Machado (Floresta, 2024)
In this study, we sought to determine the influence of combined treatments with different types of fertilizer and inoculation of the fungus Trichoderma harzianum on the growth and physiological characteristics of young plants of Cordia americana. To this end, we adopted a completely randomized experimental design, comprising six replications in a 5 × 2 factorial scheme, to assess the effects of five different types of fertilizer applied with or without T. harzianum inoculation. At 180 days post-planting, we performed measurements of plant height, stem diameter, leaf dry mass, root dry mass, stem dry mass, total dry mass, leaf area, Falker’s chlorophyll index, and chlorophyll fluorescence. It was found that the combined application of T. harzianum and a controlled-release fertilizer or manure-based organominerals was effective in enhancing the growth of C. americana plants under conditions similar to those in the field. The use of controlled-release fertilizer as a base fertilization was found to have a positive influence on all evaluated variables and was effective in maximizing the initial development of C. americana plants. Granulated fertilizers derived from swine manure were established to promote plant growth and photosynthetic efficiency, thereby confirming their efficacy as a fertilizer for the cultivation of C. americana.